1998
DOI: 10.1103/physrevb.57.9586
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric and second-harmonic spectra in antiferromagneticCr2O3

Abstract: We present a microscopic model to understand the magnetoelectric and second-harmonic spectra of Cr 2 O 3 and the interference effect between the magnetic ( m ) and electric ( e ) second-order optical polarizations. The spin-orbit interaction and the crystalline fields of correct symmetry around the Cr 3ϩ ion, i.e., the axial and twisted crystalline field of C 3 symmetry, are treated as perturbation on the trigonal states of the d 3 system of Cr 3ϩ . By these treatments we attempt to describe the observed pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 23 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…Sapphire crystals doped with transition metal such as Ti : Al 2 O 3 and Cr : Al 2 O 3 are famous laser materials, while magneto-electric characteristics and second harmonic spectra of Cr 2 O 3 with the same corundum structure as Al 2 O 3 have been studied experimentally and theoretically. The optical responses of both these doped and pure crystals have been successfully analyzed by the localized model of electronic excitation between multiplets of (3d)-electrons in the transition metal [1,2]. Hereafter, we call it d-d transition.…”
Section: Introductionmentioning
confidence: 99%
“…Sapphire crystals doped with transition metal such as Ti : Al 2 O 3 and Cr : Al 2 O 3 are famous laser materials, while magneto-electric characteristics and second harmonic spectra of Cr 2 O 3 with the same corundum structure as Al 2 O 3 have been studied experimentally and theoretically. The optical responses of both these doped and pure crystals have been successfully analyzed by the localized model of electronic excitation between multiplets of (3d)-electrons in the transition metal [1,2]. Hereafter, we call it d-d transition.…”
Section: Introductionmentioning
confidence: 99%
“…The optical responses of both these doped and pure crystals have been successfully analyzed by the localized model of electronic excitation between 3d-orbitals of the transition metal [1,2]. Hereafter we call them d-d transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that the rotation is reasonably large and readily observable, of order 10 −4 , illustrating the well-known fact that symmetry arguments are quite powerful in predicting the existence of exotic effects, but not necessarily their magnitude. More recently, microscopic theories that include spin-orbit coupling have brought theory and experiment into agreement [20][21][22].…”
mentioning
confidence: 99%